An efficient Real Time Multi View Face Recognition System - Aymen Dawood Salman, Dr.; Saman Hamid, Dr.; Ghaida Muttasher Abdulsaheb, Dr.; Dheayah Jaffar, Noor (International Journal of Engineering and Technology, 2018)
In recent years, the biometrics environment has received considerable attention at the global level. One of the most important biometrics is the face recognition. Viola and Jones algorithm is used for front face detection. Facial side images detected through the skin detection methodology. For features extraction step, Histogram oriented gradient (HOG) algorithm is used. This paper suggested using Raspberry pi3 platform in the real time multi-face recognition system to connect three cameras. In the recognition step, Support Vector Machine (SVM) used and compared with the performance of the principal component analysis algorithm (PCA). The system is tested on multiple images of the FEI database.Â Â